Between individualization and politicization: young people's interpretation patterns and action orientations in the face of climate change - Reuter, Leonie; Frick, Vivian (Frontiers in Political Science, 2024)
This paper examines the prevailing interpretation patterns and action orientations regarding climate change and climate protection among the young generation (14–22 years) in Germany. Based on a representative survey, we investigate which climate action options are currently favored and widespread among young individuals in Germany, encompassing both private sphere behavior—sustainable consumption—and public sphere behavior—collective climate action and civic engagement. Subsequently, through qualitative interviews, we delve into the shared interpretation patterns that young individuals draw upon to comprehend, evaluate, and guide their actions in climate protection. In this process, an individualizing and a politicizing interpretation pattern are identified and juxtaposed. As a result, both the representative survey and the qualitative analysis underscore a deep-rooted and widespread adoption of the individualizing rationale among young people in interpreting and acting on climate change. We discuss this finding by exploring the discursive origins of the dominant interpretation pattern and by questioning the respective transformative potential of both the individualizing and the politicizing action orientation.